2017
DOI: 10.1007/s00382-017-3997-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in terrestrial near-surface wind speed and their possible causes: an overview

Abstract: drag forces are caused by changes in the external and internal friction in the atmosphere. Changes in surface friction are mainly caused by changes in the surface roughness due to land use and cover change (LUCC), including urbanization, and changes in internal friction are mainly induced by changes in the boundary layer characteristics. Future studies should compare the spatio-temporal differences in SWS between high and low altitudes and quantify the effects of different factors on the SWS. Additionally, in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 174 publications
(261 reference statements)
6
130
0
1
Order By: Relevance
“…This change in the dynamic of the tropical atmosphere is well observed in the multi-reanalysis agreement map (Figure 4f), where all five reanalyses depict a significant trend over several marine tropical areas in the Southern Hemisphere. This has been documented in previous studies, such as Wu et al (2018). Similarly, a significant strengthening of wind speeds is observed in the Southern Hemisphere storm track (Figure 4f).…”
Section: Differences In Long-term Trendssupporting
confidence: 89%
See 1 more Smart Citation
“…This change in the dynamic of the tropical atmosphere is well observed in the multi-reanalysis agreement map (Figure 4f), where all five reanalyses depict a significant trend over several marine tropical areas in the Southern Hemisphere. This has been documented in previous studies, such as Wu et al (2018). Similarly, a significant strengthening of wind speeds is observed in the Southern Hemisphere storm track (Figure 4f).…”
Section: Differences In Long-term Trendssupporting
confidence: 89%
“…This has been documented in previous studies, such as Wu et al . (). Similarly, a significant strengthening of wind speeds is observed in the Southern Hemisphere storm track (Figure f).…”
Section: Reanalysis Intercomparisonmentioning
confidence: 97%
“…A change in u is an important manifestation of climate change, in addition to temperature and precipitation trends. While u over oceans has been increasing during the past 30 years (Wentz et al 2007, Young et al 2011, Zheng et al 2016, u measured at in situ weather stations at 10 m above ground has significantly decreased over land, particularly in the middle to high latitudes of the Northern Hemisphere (Vautard et al 2010, McVicar et al 2012b, Wu et al 2018. This phenomenon has been referred to as terrestrial stilling (Roderick et al 2007), and it has important scientific, socioeconomic, and environmental implications for fields including, but not limited to, agriculture and hydrology (McVicar et al 2012a), wind energy (Pryor et al 2006), the insurance sector (Sparks et al 1994), air pollution dispersion (McVicar and Roderick 2010), dust storms (Cowie et al 2013, Fan et al 2014, extreme temperatures (Horton et al 2015) and wind-related hazards and catastrophes (Kim and Paik 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one of the most direct impacts of stilling is on long-term wind power industry that is rapidly developing and requires large infrastructural investments. So far, the drivers and physical mechanisms behind terrestrial stilling have not been determined, and thus it is unclear whether the observed stilling will continue (Vautard et al 2010, Peterson et al 2011, McVicar et al 2012b, Wu et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in wind have broad environmental and socioeconomic implications, affecting the air quality in economically developed regions (Cai et al 2017, Pei and, the surface evaporation (Rayner 2007, McVicar et al 2012 and the wind energy resource Barthelmie 2010, Rasmussen et al 2011). As the climate warms, near surface wind speed (NSWS) over land, commonly referred to the 10 m wind speed, has declined over the past decades (Tuller 2004, Smits et al 2005, Mahowald et al 2007, McVicar et al 2008, Pryor et al 2009, Vautard et al 2010, Jiang et al 2010b, Wu et al 2018. Roderick et al (2007) firstly referred to this widespread phenomenon as 'terrestrial stilling'.…”
Section: Introductionmentioning
confidence: 99%